Lego Star wars : character encyclopedia - Hannah Dolan; Kosora, Tori.; Clare, Hibbert; Last, Shari (London : DK, 2024)
Provides an overview of all the versions of the LEGO Star Wars minifigures that have been released, with information on the sets they were available in, their accessories, and the differences between them.
Includes index.
May include Lego minifigure.
6.9
3-6.
3-6
Keywords: LEGO toys -- Juvenile literature; Models and modelmaking -- Juvenile literature; Star Wars films -- Juvenile literature; LEGO toys; Models and modelmaking; Star Wars films; LEGO toys; Models and modelmaking; Star Wars films